The view of patients and patients' companions regarding patients' rights: a phenomenological research - Jolaee S; Nikbakht Nasrabadi A; Parsa Yekta Z (Tehran University of Medical Sciences, 2004)
Introduction: Patients' rights have been center of attention in recent decades because of patients' vulnerability and worldwide sensitivity to human rights. Materials and Method: The current study is a qualitative, phenomenological research which has been carried out in Emam Khomeini Hospital during 2004-2005. The aim of this research was to identify the meaning of patient's rights from the view point of patients and/or their companions. To achieve this, 16 semi-structured interviews were conducted with 12 informants. They were asked to explain their experience regarding the patient's rights. All interviews were recorded. Data analyzing was simultaneously carried out using thematic analysis method. Results: The emerging themes included expectation for equality and justice in receiving health care services, human respect and privacy; need to be informed regarding their diagnosis and having essential facilities in the hospital. Conclusion: It appears that whether the participants are aware of patients' bill of rights or not, they are able to define some rights for themselves. Attention to theses rights can help policy makers to design unique patients' bill of rights according to Iranian sociocultural and economic situation.